Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula - Murányi, Dávid; Hwang, Jeong Mi (Zootaxa, 2017)
Two new species of Korean needleflies, Perlomyia koreana sp. n. and P. lamellata sp. n. are described from North and South Korea. Additionally, two species, Paraleuctra paramalaisei sp. n. and Perlomyia baei sp. n. are described from South Korea. The previously unknown male of Perlomyia martynovi (Zhiltzova, 1975) is described from South Korean specimens associated with females. Leuctra fusca tergostyla Wu, 1973 comb. n. is proposed for the Far Eastern populations of the Eurosiberian L. fusca (Linnaeus, 1758). Three Leuctridae genera and species are reported from North Korea for the first time and three species are new country records for South Korea. The number of stonefly species known from the Korean Peninsula is increased to 82. A key is presented for the Leuctridae species known from Korean Peninsula including taxa that are expected to occur. Distributional maps are presented and additional notes on the habitats of Korean Leuctridae are given.